Secure and User-Friendly Smart Home Automation: A Mobile-Centric IoT Approach - Matura, Rishi; Kunal (Journal of Trends in Computer Science and Smart Technology, 2024)
Home automation systems (HAS), leveraging the power of the Internet of Things (IoT), are gaining significant attention for their potential to reduce costs, labor, and human error. As the demand for smart home technologies grows, effective energy management and cost reduction become increasingly important. This research explores the technical landscape of IoT-based HAS, focusing on remote control and management of home appliances through smartphones and dedicated applications. A comparative analysis of various HAS solutions will be conducted to evaluate their functionality, usability, and energy efficiency. Additionally, the study will examine the security and privacy implications of IoT-based home automation and potential barriers to adoption such as cost and complexity. By addressing these key issues, this research aims to contribute to the development of more effective and accessible smart home solutions.
Keywords: Automation; IoT; Intelligence; smart home systems; Zigbee; Raspberry Pi; Arduino